Material Hardship in Families With Low Income: Positive Effects of Coparenting on Fathers’ and Mothers’ Parenting and Children’s Prosocial Behaviors - Lee, Joyce Y.; Volling, Brenda L.; Lee, Shawna J. (Frontiers in Psychology, 2021)
Families with low income experience high levels of economic insecurity, but less is known about how mothers and fathers in such families successfully navigate coparenting and parenting in the context of material hardship. The current study utilized a risk and resilience framework to investigate the underlying family processes linking material hardship and children’s prosocial behaviors in a sample of socioeconomically disadvantaged mother-father families with preschoolers from the Building Strong Families project (N = 452). Coparenting alliance and mothers’ and fathers’ responsive parenting were examined as mediators. Results of structural equation modeling showed that coparenting alliance was associated with higher levels of both mothers’ and fathers parenting: Subsequently, both parents’ responsive parenting were associated with higher levels of children’s prosocial behaviors. Material hardship was not associated with either parent’s responsive parenting. Tests of indirect effects confirmed that the effects of the coparenting alliance on children’s prosocial behaviors were mediated through both mothers’ and fathers’ responsive parenting. Overall, these results suggest that when mothers and fathers have a strong coparenting alliance, they are likely to withstand the negative effects of material hardship and thus engage in positive parenting behaviors that benefit their children’s prosocial development. Family strengthening interventions, including responsible fatherhood programs, would do well to integrate a strong focus on enhancing a positive coparenting alliance between mothers and fathers.